Kinetics of interferon-gamma (IFN-gamma) release in the peripheral blood of calves vaccinated with BCG - Ameni, G.; Tibbo, Markos (Informa UK Limited, 2002)
A study was conducted on 13 Friesian-Zebu crossbred calves, the ages of which lie between 6 and 18 months, to investigate the kinetics of IFN-y release in the peripheral blood following Bacille Calmete Guerine (BCG) vaccination. After being screened for bovine tuberculosis (BTB), the calves were vaccinated with 1 m L inoculums containing 6 x 10 6 CFU of BCG. The level of IFN-y in the peripheral blood was measured two times before vaccination and seven times after vaccination, using a sandwich ELISA. The kinetics of IFN-y post vaccination presented itself in three phases: rising, falling, and steady phases. The concentration of IFN-y, before and after vaccination, both in stimulated and non-stimulated samples, was statistically significant (P < 0.01). Strong positive correlation (r-0.86) was recorded between the levels of IFN-y release in avian PPD- and bovine PPD-stimulated samples. Of the total 13 calves, 11 (84.6%) reacted positively to tuberculin inoculation 15 weeks post vaccination. It is concluded that the 1FN-y rises immediately after BCG vaccination, reaching its peak two weeks post vaccination, and then declines gradually in the following weeks. The strong positive reaction of calves to tuberculin inoculation 15 weeks post vaccination showed the capability of' BCG in causing the release of IFN-y in the peripheral blood, indicating its role in protection against infection with Mycobacterium bovis in calves.